2012
DOI: 10.1124/dmd.112.049718
|View full text |Cite|
|
Sign up to set email alerts
|

Gestational Age-Dependent Changes in Gene Expression of Metabolic Enzymes and Transporters in Pregnant Mice

Abstract: Pregnancy-induced changes in drug pharmacokinetics can be explained by changes in expression of drug-metabolizing enzymes and transporters and/or normal physiology. In this study, we determined gestational age-dependent expression profiles for all metabolic enzyme and transporter genes in the maternal liver, kidney, small intestine, and placenta of pregnant mice by microarray analysis. We specifically examined the expression of genes important for xenobiotic, bile acid, and steroid hormone metabolism and dispo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
51
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 45 publications
(62 reference statements)
12
51
1
Order By: Relevance
“…3A). This activation of mOct3 mRNA in mouse placenta between early and middle pregnancy was also previously noticed by other investigators (Zwart et al, 2001;Shuster et al, 2013). Using LC-MS/MS, we further showed that mOct3 protein levels in the mouse placenta also increased dramatically at gd 15 and 19 (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…3A). This activation of mOct3 mRNA in mouse placenta between early and middle pregnancy was also previously noticed by other investigators (Zwart et al, 2001;Shuster et al, 2013). Using LC-MS/MS, we further showed that mOct3 protein levels in the mouse placenta also increased dramatically at gd 15 and 19 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Although the effect of pregnancy on mRNA expression of drug transporters has been analyzed in large-scale microarray studies and/or in tissue-specific manners in pregnant animal models (Shuster et al, 2013;Yacovino et al, 2013), comprehensive and quantitative mRNA analysis of polyspecific OC transporters has not been performed. Furthermore, few studies have quantified and compared the protein levels of OC transporters between nonpregnant and pregnant states.…”
Section: Introductionmentioning
confidence: 99%
“…This study further confirmed that hepatic CYP3A activity in pregnant mice is induced in a gestational age-dependent manner. It is not known which mouse CYP3A isoforms are responsible for increased glyburide metabolism during pregnancy as we and others have shown that mRNA levels of Cyp3a16, Cyp3a41, and Cyp3a44 are induced, whereas Cyp3a11, Cyp3a13, and Cyp3a25 genes are downregulated in a gestational age-dependent manner (Zhang et al, 2008;Shuster et al, 2013). Increases in V ss and V b most likely reflect increases in total body water and fat content during pregnancy, and further suggest that distribution of glyburide into maternal tissues is increased during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, M1 undergoes glucuronidation mediated by uridine 59-diphospho-glucuronosyltransferases (UGTs) and M2b is excreted unchanged in the urine (Naraharisetti et al, 2007). UGT1A1 and UGT1A4 expression is indeed induced during human pregnancy (Feghali and Mattison, 2011); however, mRNA levels of UGTs in pregnant mice are relatively unchanged (Shuster et al, 2013). Mechanisms of renal clearance (i.e., active tubular secretion and/or reabsorption) remain unknown for all glyburide metabolites Fetal/ maternal plasma glyburide concentration ratios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation